2013
DOI: 10.1179/1362171812y.0000000083
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of diffusion bonded titanium/304 stainless steel joint with pure Ag interlayer

Abstract: In the present study, diffusion bonding of commercially pure titanium to 304 stainless steel (SS) using a pure Ag interlayer was carried out. It is found that the pure Ag interlayer can effectively block the interdiffusion and interaction between Ti and SS. The resultant joints were composed of Ti substrate, Ti-Ag solid solution, TiAg intermetallic phase, the remnant Ag interlayer and SS. Upon tensile loading, fracture took place through the remnant Ag interlayer, indicating that the TiAg intermetallic phase e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…and WZ, similar TZs are commonly observed in dissimilar metal welding of titanium to steel[16,19]. In addition, Chu et al[20] also reported a similar TZ in the welding of CP-Ti/X65 bimetallic sheets.…”
supporting
confidence: 65%
“…and WZ, similar TZs are commonly observed in dissimilar metal welding of titanium to steel[16,19]. In addition, Chu et al[20] also reported a similar TZ in the welding of CP-Ti/X65 bimetallic sheets.…”
supporting
confidence: 65%
“…However, significant differences in the physical properties of these two dissimilar materials, such as their linear thermal expansion coefficient and melting point, can introduce considerable residual stress. Metallurgical incompatibility will result in the formation of brittle Ti-Fe series intermetallic compounds (IMCs), severely deteriorating the joint strength [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A rational solder is usually chosen as the middle transition layer to block the formation of brittle intermetallic compounds (IMCs) at the titanium alloy/stainless steel interface. Existing research indicates that welding the solid phase with the addition of an intermediate transition metal was an effective method to achieve a reliable connection between titanium alloy and stainless steel [ 4 , 8 , 9 , 10 ]. Parameters such as welding current, welding time and electrode pressure are important to consider in resistance spot welding.…”
Section: Introductionmentioning
confidence: 99%
“…By adding a ductile interlayer with appropriate melting temperature, the joint may possess a good high-temperature performance and the residual stresses presented at the joint interface could be well relieved. 14,15 Consequently, the diffusion bonding is an alternative method for preparing high-temperature joint of the SiBCN-based composites. However, no study on the diffusion bonding of SiBCN has been reported to the best of our knowledge, and more efforts are still needed in this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Silver is an attractive interlayer because of its chemical inertness and excellent ductility. 15 The alloying additive of palladium not only provides a higher melting temperature and corrosion resistance, but also maintains the low yield strength and high plasticity of the interlayer. 16,17 Prior to the joining, a dense and uniform Ti is coated on the ceramic surface by magnetron sputtering, to make the diffusion process more time effective and prevent the possible Pd-ceramic reaction.…”
Section: Introductionmentioning
confidence: 99%